National Study of Health Insurance Type and Reasons for Emergency Department Use - Capp, Roberta (Springer US, 2013)
BACKGROUND: The rates of emergency department (ED) utilization vary substantially by type of health insurance, but the association between health insurance type and patient-reported reasons for seeking ED care is unknown. OBJECTIVE: We evaluated the association between health insurance type and self-perceived acuity or access issues among individuals discharged from the ED. DESIGN, PATIENTS: This was a cross-sectional analysis of the 2011 National Health Interview Survey. Adults whose last ED visit did not result in hospitalization (n = 4,606) were asked structured questions about reasons for seeking ED care. We classified responses as 1) perceived need for immediate evaluation (acuity issues), or 2) barriers to accessing outpatient services (access issues). MAIN MEASURES: We analyzed survey-weighted data using multivariable logistic regression models to test the association between health insurance type and reasons for ED visits, while adjusting for sociodemographic characteristics. KEY RESULTS: Overall, 65.0 % (95 % CI 63.0–66.9) of adults reported ≥ 1 acuity issue and 78.9 % (95 % CI 77.3–80.5) reported ≥ 1 access issue. Among those who reported no acuity issue leading to the most recent ED visit, 84.2 % reported ≥ 1 access issue. Relative to those with private insurance, adults with Medicaid (OR 1.05; 95 % CI 0.79–1.40) and those with Medicare (OR 0.98; 95 % CI 0.66–1.47) were similarly likely to seek ED care due to an acuity issue. Adults with Medicaid (OR 1.50; 95 % CI 1.06–2.13) and Medicaid + Medicare (dual eligible) (OR 1.94; 95 % CI 1.18–3.19) were more likely than those with private insurance to seek ED care for access issues. CONCLUSION: Variability in reasons for seeking ED care among discharged patients by health insurance type may be driven more by lack of access to alternate care, rather than by differences in patient-perceived acuity. Policymakers should focus on increasing access to alternate sites of care, particularly for Medicaid beneficiaries, as well as strategies to increase care coordination that involve ED patients and providers. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11606-013-2734-4) contains supplementary material, which is available to authorized users.